Theorising MSMEs in Contexts of Urban Violence. Issue 2 (23rd February 2021) - Ganson, Brian; Hoelscher, Kristian
What are the relationships between and among small businesses, conflict, and peaceful development in contexts of urban violence? Here, the complex formal and informal divisions of economic, political and social power, authority, and legitimacy – and the many grey areas between legality and illegality, necessity and opportunism – create challenging conditions for business operations and for peacebuilding. A grounded understanding is required if peace- and development-positive interventions are to be successful. Yet both the peacebuilding and development potential of micro, small, and medium enterprises (MSMEs), and the specific dynamics of business and conflict in urban spaces, are underdeveloped in the literature assessing and promoting business potential to catalyse positive change. We therefore extract from a broad range of literature a typology representing the weight of the extant frameworks for understanding MSMEs in contexts of urban violence. We then use primary research to construct inductively a framework that captures how those living with urban violence themselves perceive businesses, their relationships to violence, and their impacts on in/security and under/development. Drawing out key areas of synthesis and tension, we propose directions for future study and practice related to small businesses in violent cities, emphasising the need to eschew simple understandings of actors, agency, and objectives in favour of a more nuanced and humane inquiry into the pain and potential inherent in the local context.